The relationship between the consumer price index and macroeconomic policy variables in North African countries (2001-2020) - Rebahi, Ibrahim; Hamani, Abderraouf (International journal of economic perspectives, 2024)
This research paper deals with the relationship between the consumer price index and the macroeconomic policy variables (LG, M2 and EXCH), in the North African countries (Algeria, Tunisia, Egypt and Morocco), in the period (2001-2020). The study relied on the Panel Vecm model in order to show this relationship in the long and short run. This study was found that there is at least one cointegration relationship, through tests of (Pedroni, Kao and Johanssen), the stability of the variables in the first differences, and the rate of return to equilibrium was determined, which was estimated at 3.5% per year, which showed the extent of the weakness of the economies of the selected countries in fixing the various imbalances that occurred.